Powinności w perspektywie kategorii znikomej społecznej szkodliwości czynu – orzecznictwo. - Kozielewicz, Wiesław (Kwartalnik Prawa Publicznego, 2016)
The Polish Criminal Code of 1997 adopted a regulation that a prohibited act of negligible social harmfulness does not constitute a crime. The notion of „social harmfulness” has replaced the concept of „social danger of action”, originated from Soviet law dating back to 1950. In the case law of the Supreme Court, until the entry into force of the Criminal Code of 1997, it has been repeatedly stressed that once a negligible social danger of the action is confirmed, the proceedings should be discontinued. The applicable Criminal Code lists the circumstances that the court takes into account while evaluating the degree of social harmfulness. Referring to them, the Supreme Court points out the predominant importance of circumstances that are the subject of a prohibited offense. In its case law, the Supreme Court emphasizes that the statutory duty of every court analizing a criminal case is always to assess the degree of detriment of the act. The Supreme Court points out that such an assessment may take place only after it has been confirmed that the culpable conduct of the accused has fulfilled all the marks of the prohibited act.